The Influence Of Msmes, Inflation, And Sharia Bank Finance On Economic Growth - Alfian Eka Saputra; Zulpahmi Zulpahmi; Arief Fitriyanto (ITB AAS INDONESIA Surakarta, 2023)
Economic growth is important to study considering that each region will always try to increase its economic target. This study aims to analyze regional economic growth in West Java with the predictor variables of the number of MSMEs, inflation, and Islamic bank financing. Using secondary data for the 2016–2021 period obtained from the Central Bureau of Statistics, the Services and Finance Authority, and the Office of Cooperatives and UMKM of West Java Province, Using seven cities in West Java as a sample in the study and multiple linear regression as an analytical tool The findings revealed that, for the 2016–2021 period, the number of MSMEs, inflation, and Islamic bank financing had a significant positive effect on West Java regional economic growth. Furthermore, simultaneously, the three independent variables significantly affect the regional economic growth of West Java. West Java's regional economic growth variable of 95.28% is influenced by the independent variables of the number of MSMEs, inflation, and Islamic bank financing, while 4.72% is influenced by other variables. In order to increase economic growth, the government's role is very important in empowering MSMEs, maintaining inflation rate stability, and increasing the portion of sharia financing by Islamic banks.